DYNAMICS OF MORTALITY RATE FROM THE DISEASES OF ENDOCRINE SYSTEM IN THE ALTAI KRAI - Юрий Юрьевич Дорофеев; Владимир Борисович Колядо; Елена Владимировна Колядо; Сергей Иванович Трибунский (Медицина в Кузбассе)
Object of the research (observation). Mortality rate of the population from the diseases of endocrine system.